Pulmonary Nocardiosis: Review of Cases and an Update - Malini Shariff; Jayanthi Gunasekaran (Canadian Respiratory Journal)
Nocardia, a branching, filamentous bacteria, is widely distributed in the environment and can cause human infection in immune-compromised hosts. Inhalation of Nocardia leads to pulmonary disease. Microbiology laboratory processed the clinical samples from patients with respiratory infections. Smears were prepared from the samples and were stained and cultured. Five cases were positive for Nocardia. They were treated with the trimethoprim-sulfamethoxazole combination. The disease was cured in three patients, and two died due to other comorbid conditions leading to complications. Nocardiosis is encountered in parts of the world even where it is not endemic due to increased world travel. So physicians and laboratory staff should be aware of this and try to diagnose it. Early detection can lead to the prompt initiation of treatment and reduced mortality in these patients. Patients with disseminated or severe nocardiosis should be treated with combination therapy with two or more active agents.